From Classroom to Studio: How Talk Show Simulations Shape Students’ Consecutive Interpreting Skills - Dian Heriani; Winda Syafitri; Nasha Fathimah; Qaila Tavana Putri Nazala (Talenta Publisher, 2026)
This study examined how talk show simulations serve as a pedagogical bridge between classroom-based interpreting instruction and real-world performance demands, specifically in consecutive interpreting. While simulation-based learning has gained increasing attention in translation and interpreting studies, empirical research on talk show–based simulation for interpreting programs in Indonesia remains limited. This mixed-methods study investigated students’ perceptions, challenges, and skill development after engaging in structured talk show simulations over one academic semester. Data were collected from 21 undergraduate interpretation students through questionnaires, performance assessments, and semi-structured interviews. The findings have revealed that simulation of talk shows can be an efficient tool in developing note-taking techniques, fluency in delivery of answers, retention of the information in the memory, as well as speaker and listener coordination techniques among the participants. The students, however, experienced problems in other areas as well. The study concluded that talk show simulations provide an authentic, high-engagement learning environment that strengthens students’ consecutive interpreting competencies while fostering professional readiness. Implications for curriculum design and interpreter training are discussed.